ICU Admission Source as a Predictor of Mortality for Patients With Sepsis. (September 2018) - Motzkus, Christine A.; Chrysanthopoulou, Stavroula A.; Luckmann, Roger; Rincon, Teresa A.; Lapane, Kate L.; Lilly, Craig M.
Purpose: Sepsis is the leading noncardiac cause of intensive care unit (ICU) death. Pre-ICU admission site may be associated with mortality of ICU patients with sepsis. This study quantifies mortality differences among patients with sepsis admitted to an ICU from a hospital ward, emergency department (ED), or an operating room (OR). Methods: We conducted a retrospective cohort study of 1762 adults with sepsis using ICU record data obtained from a clinical database of an academic medical center. Survival analysis provided crude and adjusted hazard rate ratio (HRR) estimates comparing hospital mortality among patients from hospital wards, EDs, and ORs, adjusted for age, sex, and severity of illness. Results: Mortality of patients with sepsis differed based on the pre-ICU admission site. Compared to patients admitted from an ED, patients admitted from hospital wards had higher mortality (HRR: 1.35; 95% confidence interval [CI]: 1.09-1.68) and those admitted from an OR had lower mortality (HRR: 0.37; 95% CI: 0.23-0.58). Conclusion: Patients with sepsis admitted to an ICU from a hospital ward experienced greater mortality than patients with sepsis admitted to an ICU from an ED. These findings indicate that there may be systematic differences in the selection of patient care locations, recognition, and management of patients with sepsis that warrant further investigation.